Reactive oxygen species are responsible for the cell aggregation and production of pro-inflammatory mediators in phorbol ester (PMA)-treated U937 cells on gelatin-coated dishes through upregulation of autophagy. (4th July 2019) - Zhao, Ye-Li; Zhang, Xuan; Liu, Wei-Wei; Yang, Yu-Ting; Gao, Zhuo-Kun; Liu, Xiao-Ling; Liu, Wei; Hayashi, Toshihiko; Yamato, Masayuki; Fujisaki, Hitomi; Hattori, Shunji; Mizuno, Kazunori; et al.
ABSTRACT: Purpose : Our previous studies indicate that phorbol 12-myristate 13-acetate (PMA)-treated U937 cells cultured on collagen I-coated dishes express lowered production of pro-inflammatory mediators in parallel through reduced reactive oxygen species (ROS) levels. By contrast, PMA-treated U937 cells on gelatin, the denatured collagen, show enhanced production of pro-inflammatory mediators, mediated by up-regulating autophagy levels. The present study is aimed to investigate the effect of ROS levels in PMA-treated U937 cells cultured on gelatin-coated surface. Material and methods : MTT assay, flow cytometric analysis of ROS and autophagy, biochemical detection of antioxidant levels, enzyme-linked immunosorbent assay, and western blot were used. Results : Gelatin-coating increased ROS levels in PMA-treated U937 cells. Increased ROS levels are involved in the regulation of cell aggregation and the release of pro-inflammatory mediators in gelatin-coated culture. These results lead to the query about the crosstalk between the two positive regulators, the autophagy and ROS. Autophagy induction is attenuated by N -acetyl-L-cysteine treatment, but the treatment with autophagy inhibitor, 3-methyladenine, does not affect ROS levels, suggesting ROS are upstream of autophagy in the regulation axis of differentiated U937 cells on gelatin-coated surface. Further study confirmed that upregulation of autophagy was responsible for ROS-induced cell aggregation and production of pro-inflammatory mediators. Conclusion : The results suggest that gelatin-coating promotes the aggregation of PMA-treated U937 cells and the production of pro-inflammatory mediators by ROS-autophagy signaling pathway.